2021
DOI: 10.3390/en14113165
|View full text |Cite
|
Sign up to set email alerts
|

Economic Development, CO2 Emissions and Energy Use Nexus-Evidence from the Danube Region Countries

Abstract: The aim of this study is to examine the empirical cointegration, long-run and short-run dynamics and causal relationships between carbon emissions, energy consumption and economic growth in 14 Danube region countries over the period of 1990–2019. The autoregressive distributed lag (ARDL) bounds testing methodology was applied for each of the examined variables as a dependent variable. Limited by the length of the time series, we excluded two countries from the analysis and obtained valid results for the others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Bekun et al [12] found a negative relationship between economic growth and CO 2 emissions in South Africa. In contrary to most studies, Litavcova and Chovancova [13] obtained varying relationships between economic growth, carbon emissions, and energy consumption for 14 Danube region countries. Another study by Rahman et al [14] concluded that carbon emissions and population density had unidirectional positive effect on the economic growth in the long run, with this relation became bidirectional in the short run for five South Asian countries: Bangladesh, India, Nepal, Pakistan and Sri Lanka.…”
Section: The Nexus Between Co 2 Emissions and Economic Growthmentioning
confidence: 60%
“…Bekun et al [12] found a negative relationship between economic growth and CO 2 emissions in South Africa. In contrary to most studies, Litavcova and Chovancova [13] obtained varying relationships between economic growth, carbon emissions, and energy consumption for 14 Danube region countries. Another study by Rahman et al [14] concluded that carbon emissions and population density had unidirectional positive effect on the economic growth in the long run, with this relation became bidirectional in the short run for five South Asian countries: Bangladesh, India, Nepal, Pakistan and Sri Lanka.…”
Section: The Nexus Between Co 2 Emissions and Economic Growthmentioning
confidence: 60%
“…According to the works of Odugbesan and Rjoub [55] and Litavcová and Chovancová [51], the variables GDP per capita and the level of energy consumption were logarithmized and the following abbreviations used: l_Country_GDP, l_Country_E, and the level of CO 2 consumption, as Country_CO 2 (where Country was a prefix for the analyzed country: (CZ, Czech Republic; PL, Poland; SL, Slovakia; HU, Hungary).…”
Section: Methodsmentioning
confidence: 99%
“…The development of scientific research in the discussed area also contributed to the extension of the research apparatus with more and more complex econometric models. As a result, numerous scientific publications appeared, among which these works deserved attention: Apergis and Payne [47], Bartleet and Gounder [48], Arouri et al [49], Papiez [50], Jóźwik, Gavryshkiv and Gruszecki [21], and Litavcová and Chovancová [51]. Econometric analyses of the interrelationships of variables such as GDP, CO 2 emissions, and energy consumption have been carried out all over the world, covering different countries, time periods, and using more and more refined econometric methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The causal relationships between carbon emissions, energy consumption and economic growth were analyzed by Litavcová and Chovancová (2021). The analysis covers 14 Danube region countries over the period of 1990-2019 and is based on the ARDL approach.…”
Section: Previous Research On the Subjectmentioning
confidence: 99%